The beginnings of modern storytelling in Turkish literature (Multidisciplinary Journal of Science and Technology, 2025)
The emergence of modern storytelling in Turkish literature marks a transformative period characterized by a shift from traditional oral and poetic forms to innovative narrative techniques influenced by Western literary models. This evolution, beginning in the late Ottoman era and accelerating during the early Republican period, reflects broader socio-cultural changes, including modernization, secularization, and the rise of nationalism. Pioneering authors such as Ahmet Mithat Efendi, Namık Kemal, and later Ömer Seyfettin and Halide Edip Adıvar, played crucial roles in introducing novelistic forms, short stories, and realistic portrayals of society. These works blended indigenous themes with universal literary trends, exploring issues of identity, gender, and social reform. This article examines the historical context, key figures, and stylistic innovations that shaped the beginnings of modern storytelling in Turkish literature, highlighting its lasting impact on contemporary Turkish narrative traditions.